Autoantibody Signaling in Pemphigus Vulgaris: Development of an Integrated Model - Sajda, Thomas; Sinha, Animesh A. (Frontiers in Immunology, 2018)
Pemphigus vulgaris (PV) is an autoimmune skin blistering disease effecting both cutaneous and mucosal epithelia. Blister formation in PV is known to result from the binding of autoantibodies (autoAbs) to keratinocyte antigens. The primary antigenic targets of pathogenic autoAbs are known to be desmoglein 3 (Dsg3), and to a lesser extent, desmoglein 1 (Dsg1), cadherin family proteins that partially comprise the desmosome, a protein structure responsible for maintaining cell adhesion, although additional autoAbs, whose role in blister formation is still unclear, are also known to be present in PV patients. Nevertheless, there remain large gaps in knowledge concerning the precise mechanisms through which autoAb binding induces blister formation. Consequently, the primary therapeutic interventions for PV focus on systemic immunosuppression, whose side effects represent a significant health risk to patients. In an effort to identify novel, disease specific therapeutic targets, a multitude of studies attempting to elucidate the pathogenic mechanisms downstream of autoAb binding have led to significant advancements in the understanding of autoAb mediated blister formation. Despite this enhanced characterization of disease processes, a satisfactory explanation of autoAb-induced acantholysis still does not exist. Here, we carefully review the literature investigating the pathogenic disease mechanisms in PV and, taking into account the full scope of results from these studies, provide a novel, comprehensive theory of blister formation in PV.